Efektivitas Kekuatan Pembuktian Keterangan Anak sebagai Korban Kekerasan dalam Sistem Peradilan Pidana - Darma, Rama Eka (CV. Social Politic Genius (SIGn), 2023)
This study aims to analyze the evidentiary strength of the statements of children in their position as witnesses to victims of violence, as well as the factors that influence the course of the trial. This research was conducted in Makassar City to be precise at the Makassar Police and Makassar District Court. Data collection techniques used in this study were interviews, documentation, and literature study. The data analysis technique used is qualitative data analysis techniques. The power of proof of testimony of children as victim witnesses is based on the evidentiary provisions in Law Number 8 of 1981. Children's statements cannot be used as evidence for valid witness testimony because they do not meet the formal requirements as evidence for witness testimony, because children are not sworn in so they are only used as evidence of clues based on the explanation in Article 171 of Law Number 8 of 1981. Therefore, evidence of clues cannot stand alone but must be supported by at least two other valid evidences. As for Article 171 of Law Number 8 of 1981 was apparently still defended in Bill Number 8 of 1981. It is better if these article must be reviewed so that the statements of child witnesses can become the main evidence, not only as evidence of clues.